2005
DOI: 10.1007/s00280-004-0944-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting BCL-2 overexpression in various human malignancies through NF-κB inhibition by the proteasome inhibitor bortezomib

Abstract: Diverse signaling pathways variably regulate BCL-2 gene expression in a cell type-specific fashion. Therapy to decrease BCL-2 levels in various human cancers would be more broadly applicable if targeted to transcriptional activation rather than signal transduction cascades. Finally, the apoptotic efficacy of proteasome inhibition with bortezomib paralleled the ability to inhibit NF-kappaB activity and decrease BCL-2 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 36 publications
4
88
0
2
Order By: Relevance
“…Another model (Willis et al, 2007) suggests that BAX/BAK are constitutively engaged and restrained by their cognate antiapoptotic guardians, and that BID and BIM simply dissociate these interactions when free to do so. Although some studies have demonstrated downregulation of BCL-2 (Fahy et al, 2005) following bortezomib, this has not been consistently observed. BCL-X L is transcriptionally regulated by NF-kB; however, inhibition of IkB proteasomal degradation has not been demonstrated to be associated consistently with downregulation of BCL-X L .…”
Section: Bcl-2 Bcl-x L A1 and Bcl-w Regulation By Bortezomibmentioning
confidence: 91%
See 1 more Smart Citation
“…Another model (Willis et al, 2007) suggests that BAX/BAK are constitutively engaged and restrained by their cognate antiapoptotic guardians, and that BID and BIM simply dissociate these interactions when free to do so. Although some studies have demonstrated downregulation of BCL-2 (Fahy et al, 2005) following bortezomib, this has not been consistently observed. BCL-X L is transcriptionally regulated by NF-kB; however, inhibition of IkB proteasomal degradation has not been demonstrated to be associated consistently with downregulation of BCL-X L .…”
Section: Bcl-2 Bcl-x L A1 and Bcl-w Regulation By Bortezomibmentioning
confidence: 91%
“…G 2 -M arrest is correlated with elevation of the cyclin-dependent kinase inhibitors p21, p27, p16, p18 and p19 Ling et al, 2003a;Coquelle et al, 2006). Inhibition of nuclear factor-kB (NF-kB) has been implicated in the mechanism of toxicity of bortezomib Fahy et al, 2005). Proteasomal degradation of inhibitory-kB (IkB) enables NF-kB release, its nuclear translocation and function as a transcriptional activator of antiapoptotic oncogenes including BCL-X L and A1 (Zabel and Baeuerle, 1990;Anan et al, 2006).…”
Section: Proteasome Regulation By Polyubiquitinationmentioning
confidence: 99%
“…For example, Bax, which can exist as a homodimer, is also able to form a heterodimer with Bcl-2. Overexpression of Bax in several cell lines counteracts the effect of Bcl-2 [25][26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…Other proteins, such as Bcl-x L , have the same anti-apoptotic function, but several molecules of the same family, such as Bcl-xS and Bax-alpha, can trigger the opposite effect. Bcl-2 can interact with other proteins [26][27][28] . For example, Bax, which can exist as a homodimer, is also able to form a heterodimer with Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…37 For example, preclinical studies indicate that the apoptotic efficacy of proteasome inhibition with bortezomib (PS-341, Velcade) inhibits NF-jB activity and decreases Bcl-2 levels in several human cancer cell lines, including androgen-independent PC-3 prostate cancer cells. 38 Chemotherapeutic agents, including docetaxel, induce NF-jB activation, impeding apoptotic signaling in cancer cells. Cotreatment with docetaxel and an inhibitor of IjB kinase-2, PS-1145, reportedly prevented docetaxel-induced mTOR indicates mammalian target of rapamycin, Bcl-2, B-cell chronic lymphocytic leukemia/lymphoma 2; Bcl-X L , BCL2-like 1; XIAP, X-linked inhibitor of apoptosis; NF-jB, nuclear factor jB; Bax, BCL21-associated X protein; Bad, BCL2-antagonist of cell death; FLIP S , Fas-associated death domain (FADD)-like interleukin-1b-converting enzyme (FLICE)-inhibitory protein S; PDK1, 3-phosphoinositide-dependent protein kinase 1; TRAIL, tumor necrosis factor-related apoptosis-inducing ligand; DR4/DR5, TRAIL death receptors 4 and 5; siRNA, small-interfering RNA.…”
Section: Nf-jbmentioning
confidence: 99%